Organizational Performance Evaluation Using European Foundation for Quality Management (EFQM) Model: Case Study of the Central Bank of Iraq - Andraws, Rafal Saeed; Bellaaj, Moez (Journal of Ecohumanism, 2025)
This study seeks to assess the organizational performance of the Central Bank of Iraq using the European Foundation for Quality Management (EFQM 2025) model. By identifying strengths, weaknesses, and performance gaps, the research provides practical insights aimed at achieving organizational excellence and sustainability in emerging economies.The study used EFQM-aligned checklists to collect data, which were then analyzed using weighted averages and mathematical equations. Statistical tools, including SPSS and the least significant difference (LSD) test, were used to rank EFQM criteria according to their impact on improving performance quality.The Central Bank of Iraq achieved a 66.4% compliance rate with EFQM standards and excelled in areas such as organizational culture and leadership, and stakeholder engagement (88%). However, significant deficiencies were detected in strategic and operational performance (31%), highlighting critical areas for targeted improvement initiatives.While the study is limited to the Central Bank of Iraq, the EFQM framework provides a versatile tool for improving organizations in diverse contexts. Future research could explore its application across different sectors and geographies to validate the findings.This research represents a pioneering effort to apply the EFQM 2025 criteria to assess organizational performance in an emerging economy. Its findings provide practical recommendations for policy makers and practitioners, contributing to the broader discourse on quality management in dynamic environments.